2023
DOI: 10.1371/journal.pone.0282195
|View full text |Cite
|
Sign up to set email alerts
|

eHealth literacy and its associated factors in Ethiopia: Systematic review and meta-analysis

Abstract: Introduction Electronic health has the potential benefit to the health system by improving health service quality efficiency effectiveness and reducing the cost of care. Having good e-health literacy level is considered essential for improving healthcare delivery and quality of care as well as empowers caregivers and patients to influence control care decisions. Many studies have done on eHealth literacy and its determinants among adults, however, inconsistent findings from those studies were found. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Hennemann et al, 2017; Thapa et al, 2021). Similarly, most recent studies have confirmed that performance expectancy might increase the intention to use an app among physicians (Breil et al, 2022), and perceived usefulness affect positively the e-health literacy (Wubante et al, 2023), suggesting; therefore, the relevance of these factors that should be promoted during undergraduate education.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hennemann et al, 2017; Thapa et al, 2021). Similarly, most recent studies have confirmed that performance expectancy might increase the intention to use an app among physicians (Breil et al, 2022), and perceived usefulness affect positively the e-health literacy (Wubante et al, 2023), suggesting; therefore, the relevance of these factors that should be promoted during undergraduate education.…”
Section: Discussionmentioning
confidence: 85%
“…Discrepancies between high-income and low-income countries are also confirmed in the use of digital technologies for specific functions, with a poor level in several aspects in Ethiopia (Shiferaw and Mehari, 2019; Tesfa et al, 2021) and in electronic prescribing and communication in the USA and Switzerland (Duffy et al, 2016; Gaumer et al, 2007; Kocher et al, 2021). However, a recent meta-analysis suggests that more than half of a sample of 1758 adults in Ethiopia is e-health literate (Wubante et al, 2023). Therefore, further investigation is needed to explore the level of digital health literacy among HCPs in low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as World Health Organization stated that eHealth has been implemented in the absence of a careful examination of the evidence base [ 48 , 49 ], inadequate knowledge of health care providers’ eHealth literacy may be one of the reasons why Western countries have faced barriers in the implementation processes. Thus, knowledge of health care providers’ eHealth literacy seems highly relevant for countries with lower economic performance, such as Iran and Ethiopia, when developing eHealth programmes to improve the delivery of health care services [ 50 ]. However, this knowledge cannot be generalised to Western countries, where eHealth infrastructure exists to very different extent compared to non-Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the catheter type, an indwelling vascular line increases the risk of central line-associated bloodstream infections (CLABSI) [ 12 , 13 ]. The mortality rate associated with CLABSI varies from 12% to 40%, depending on factors such as patient comorbidities, catheter type, and the type of microorganism causing the infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%